2019
DOI: 10.1111/apt.15112
|View full text |Cite
|
Sign up to set email alerts
|

The willingness of patients with gastroparesis to take risks with medications

Abstract: Summary Background Gastroparesis has a significant negative impact on patients’ quality of life. Only one medication is approved for gastroparesis and it is associated with a significant risk of side effects. Aim To assess the willingness of patients to take risks associated with medications to treat gastroparesis symptoms. Methods We developed a questionnaire to assess medication risk‐taking behaviour in patients identified as having documented gastroparesis (consistent symptoms, normal upper endoscopy, delay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…8 9 The impact of gastroparesis is such that, in one study, patients were willing to accept a median 13.4% risk of death to cure their symptoms using a hypothetical medication. 10 Despite these detrimental effects, epidemiological data on this disease are limited, and most studies have been conducted in referral settings. [11][12][13][14] The only true population-based epidemiological study, from Olmsted County, Minnesota, USA, estimated the standardised prevalence of gastroparesis to be 24.2 per 100 000 persons and the standardised incidence to be 6.3 per 100 000 person-years.…”
Section: Stomachmentioning
confidence: 99%
“…8 9 The impact of gastroparesis is such that, in one study, patients were willing to accept a median 13.4% risk of death to cure their symptoms using a hypothetical medication. 10 Despite these detrimental effects, epidemiological data on this disease are limited, and most studies have been conducted in referral settings. [11][12][13][14] The only true population-based epidemiological study, from Olmsted County, Minnesota, USA, estimated the standardised prevalence of gastroparesis to be 24.2 per 100 000 persons and the standardised incidence to be 6.3 per 100 000 person-years.…”
Section: Stomachmentioning
confidence: 99%
“…15,24 GP patients with psychiatric co-morbidities tend to experience longer hospital stays and reduced work hours. 25 Psychiatric comorbidities are less common in children with GP compared with adults. In one study (n = 239), they were found in 28% of pediatric patients with GP (Table 1).…”
Section: Psychiatric Co-morbiditiesmentioning
confidence: 99%
“…70 A survey among people with gastroparesis observed a correlation between willingness to accept potentially lethal side effects and symptom severity. 76 This emphasizes how burdensome GI complications are.…”
Section: Managementmentioning
confidence: 99%